EDUCATION ON HYPERTENSION FOR EARLY PREVENTION IN BEACH LABUBAR VILLAGE - Aidha, Zuhrina; Kartika, Widia; Dwanti Pane, Shahrani; Mahardika, Rangga (LPPM Univ. Ibn Khaldun Bogor, 2022)
Generally, hypertension occurs in the elderly, but some observations prove that hypertension can grow since adolescence and its prevalence increases over a certain period of time. The causes of hypertension, including unhealthy lifestyles, environment, education, and the lack of public insight regarding the management of hypertension sufferers. The target of this service is the Labu Baru Beach community, the procedures carried out by community service are surveys and advocacy. The survey was conducted to determine the indicators of public knowledge of Labu Baru Beach about Hypertension. Advocacy is carried out in three stages, namely: 1) Providing information about hypertension problems that occur. 2) Make joint efforts to solve the problem of hypertension for the community by involving the village head, village secretary, village officials, village midwives and village cadres to provide or explain hypertension. 3) Socialization of hypertension to mothers or the local community. 4) Insight about hypertension to the local community.